Implementasi Penerjemah Bahasa Isyarat Pada Bahasa Isyarat Indonesia (BISINDO) Dengan Metode Principal Component Analysis (PCA) - Rohmat Indra Borman; Bentar Priyopradono (Politeknik Harapan Bersama, 2018)
Deaf people can communicate with other normal people by utilizing hearing impairment or by using sign language. Bahasa Isyarat Indonesia (BISINDO) is a sign language promoted by Gerakan Kesejahteraan Tunarungu Indonesia (GERKATIN). An application is required to make people easier to communicate and recognize sign language especially Bahasa Isyarat Indonesia (BISINDO). This research aimed to develop a translator application that can translate a movement of sign language into a text form that can be understood by the normal person. The method used in this research is PCA (Principal Component Analysis) to identify patterns in the data and then express the data to other forms to show differences and similarities between patterns. To recognize the object, this research used a viola-jones method that gives a specific indication of a picture or image. This research will produce an application that can translate 26 letters sign language to the form of letters in general.